What COVID-19 Taught Us About Pedagogy and Social Justice-Pandemic or Not - Brandi Lawless; Yea-Wen Chen (Central States Communication Association, 2021)
The COVID-19 pandemic (in conjunction with the Black Lives Matter Movement) exposed pervasive inequities, challenges, and opportunities to explore and implement "best" pedagogical practices to improve how we address social justice issues. Moreover, the COVID-19 pandemic intensified intergenerational gaps for the already vulnerable, under-resourced, and marginalized in our society. In response, we propose four "best practices" to embrace in our classrooms. These are: (a) fostering flexibility to bridge equity gaps; (b) rethinking the pedagogical panopticon; (c) emphasizing listening to and affirming students' struggles; and (d) employing student-centered accountability. The authors detail some specific inequalities that were brought to the surface during the Spring and Summer of 2020, offer "best practices" in response to such inequities, and stress the need for a student-centered pedagogy that serves to improve teaching and learning not just during a crisis, but also in semesters and years to come.